Pharyngocutaneous fistulas after total laryngectomy or pharyngolaryngectomy: Place of video‐fluoroscopic swallowing study. Issue 12 (30th August 2020) - Carsuzaa, Florent; Capitaine, Anne‐Laure; Ferrié, Jean‐Claude; Apert, Vincent; Tonnerre, Denis; Frasca, Denis; Dufour, Xavier
Abstract: Background: Specify place of video‐fluoroscopic swallowing study (VFS) in the decision of oral refeeding after total pharyngolaryngectomy. Methods: At postoperative day 7, a blue dye testing was performed. If negative, a VFS was performed looking for a blind fistula. If this exam was negative, oral refeeding was started, but if a blind fistula was observed, cervical compression bandage was performed. Results: In 186 patients, a VFS was performed for 142 patients with negative blue dye testing. It was negative for 98 patients (69%) and positive for 44 patients (31%) (blind fistula). Patients had a probability of 7.1% to have a secondary pharyngocutaneous fistula (PCF) if the VFS was negative, and 15.9% if it was positive. No risk factor for the development of a secondary PCF or a blind fistula emerged from our analysis. Conclusion: VFS should be performed before any oral refeeding in all patients operated with a total pharyngolaryngectomy.